Navajo - Bodden, Valerie (Mankato, Minnesota : Creative Education/Creative Paperbacks, 2018)
An introduction to the Navajo lifestyle and history, including their forced relocation and how they keep traditions alive today. A Navajo story recounts how two brothers saved humanity.
Includes bibliographical references (page 24) and index.
Keywords: Navajo Indians -- Juvenile literature; Illustrated children's books; Indians of North America -- Southwest, New; Illustrated children's books; Navajo Indians; Juvenile works; Juvenile works